Assessing Reading Strategies and Abilities of Humanities and Social Sciences Undergraduates in English Fiction and Non-Fiction Texts - Khadka, Bishnu Kumar (Spectrum of Humanities and Social Sciences, 2025)
Reading, a dynamic and multicomponent skill, plays a critical role in meaning-making, encompassing decoding, syntactic processing, vocabulary, and metacognition. This research investigates the reading comprehension abilities (RCA) and use of reading strategies by the undergraduate students of humanities and social sciences at Mid-West University (MU), Surkhet, Nepal focusing on English fiction and non-fiction texts. Employing a quantitative research method, data were gathered from 50 fourth-semester students using a reading comprehension test based on CEFR B2-level texts and a five point Likert scale measured from 1 for strongly disagree to 5 for strongly agree for positive items and reverse scoring for negative statements for assessing cognitive, metacognitive, and socio-affective reading strategies. The Findings reveal that students predominantly utilize cognitive and metacognitive strategies, with engagement in socio-affective reading practices. The majority demonstrate basic to intermediate proficiency, with notable gaps at advanced levels (C1/C2). These findings underline the need for targeted curriculum intervention emphasizing higher-order reading strategies, diverse authentic texts, and advanced-level reading resources to enhance comprehension ability in Nepali EFL contexts.